Catalpol protects AC16 cells from hypoxia/reoxygenation injury by regulating the miR‐22‐3p/DPP4 axis. Issue 6 (21st March 2022) - Li, Ziyang; Zhao, Jianrong; Li, Hui; Li, Yan; Lin, Caixia
Abstract: Catalpol (CA) is widely used in the protection of cardiomyocytes. Nevertheless, the mechanism of CA in alleviating ischemia‐reperfusion‐induced injury of cardiomyocytes remains unclear. Human cardiomyocyte AC16 cells were subjected to hypoxia/reoxygenation (H/R) injury. Quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot analysis were applied to detect tumor necrosis factor‐alpha (TNF‐α) mRNA, interleukin‐6 (IL‐6) mRNA, interleukin‐1beta (IL‐1β) mRNA, microRNA‐22‐3p (miR‐22‐3p), dipeptidyl peptidase 4 (DPP4) mRNA, and DPP4 protein expressions. The cell viability and apoptosis were measured by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) assay and flow cytometry, respectively. Lactate dehydrogenase (LDH) and creatine kinase (CK‐MB) were examined by enzyme‐linked immunosorbent assay (ELISA) kits. A dual‐luciferase reporter gene assay was performed to confirm the binding sequence between miR‐22‐3p and DPP4 mRNA 3ʹ‐untranslated region (3ʹUTR). CA promoted the viability and reduced cell apoptosis of AC16 cells and repressed the release of inflammatory cytokines TNF‐α, IL‐6, and IL‐1β, and inhibited the leakage of myocardial injury markers LDH and CK‐MB. Furthermore, CA enhanced the expression of miR‐22‐3p in cardiomyocytes, and DPP4 was validated to be the target gene of miR‐22‐3p. The inhibition of miR‐22‐3p and augmentation of DPP4 reversed the above effects of CA. CA protects A16 cells from H/R injury by regulating the miR‐22‐3p/DPP4 axis.